(untitled) (Bangladesh Journal of Livestock Research, 2025)
A baseline survey on biosecurity measurement with some background parameters of dairy farms was conducted at Gazipur sadar, Sreepur, Kapasia and Kaligonj upazilla of Gazipur district from January to June 2022. "Data were collected using a structured questionnaire through personal visits to 115 dairy farms, with assistance from a research assistant." The farm size varied from 10 to 150 dairy cattle, the majority of the farms contained between 15 to 40 dairy cattle. "Most (87.83%) of the farmers were male, while 12.17% were female." The farmers had a wide range of educational backgrounds from primary to higher secondary or above. Majority of the farmers were engaged in agriculture (24.35%) and business (31.30%). Almost all of the farmers (100%) heard about biosecurity from different sources. The majority (35.66%) of the farmers had a slight or moderate idea about biosecurity. The highest 70% of farms are located near the road and 65% of farms are located near the market in Gazipur sadar upazilla and the lowest 35% of farms are located near to another animal farms in Sreepur upazilla. The highest 50% of farms had no fencing in Kaligonj upazilla and the lowest 18% of farms had rodent-proof and wild bird-proof facilities in Kapasia upazilla. The majority (75%) of the farms did not have a separate store room in Sreepur and Kapasia upazilla. The majority of the farms had absence of a ‘no admittance’ sign, gatekeeper, foot bath at the farm gate, hand washing facilities at shed entry, use of protective/dedicated clothing and no visitor registrar maintained. The highest 76% of the farmers followed the scientific/hygienic way of milking and milk handling, and 68% followed the scientific/hygienic way of storage and transportation of milk in Sreepur upazilla. The results of this study provided a clear picture of the level of biosecurity compliance among the dairy farms of Gazipur district which will be useful for farmers and researchers to improve the biosecurity measurement that is an issue of cattle health, animal welfare, and high productivity to sustainable dairy production. Bang. J. Livs. Res. Vol. 30 (1&2), 2023: P. 11-22